Comparative Evaluation of General Oral and Periodontal Health Status of Chronic Kidney Disease (CKD) patients in Various Stages admitted to Sharif Medical and Dental College, Lahore, and Healthy Controls - Hira Butt, Nauman Rauf Khan, Muhammad Aman, Syeda Maryam Fatima, Maria Jabbar, Farooq Maqsood (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the general oral and periodontal health status of chronic kidney disease patients in various stages and compare it to healthy controls. Methodology: A Cross-sectional comparative study was conducted in Sharif Medical and Dental College, Lahore on 50 patients with chronic kidney disease and 58 controls for the time duration of one year. Data collection was based on the Community Periodontal Index of Treatment Needs and Decayed Missing and Filled index. Results: There was a significant association between stage of kidney disease and periodontal health (p= ≤0.001) and general oral health as determined by the DMFT index (≤0.001). There was a significant difference in the scores of decayed teeth between the controls and stage 3 (0.042), stage 5 (≤0.001) and stage 4 (p= 0.001). The difference in the scores of missing teeth was significant between controls and stage 5 (p=≤0.001) and stage 4 (p=0.001). Similar was the case for decayed missing and filled teeth index scores for controls and stage 3 (p=0.013), stage 5 (≤0.001) and stage 4 (≤0.001). Conclusion: Bleeding gums were most common in stage 3 while pocket depths of 4-5mm were highest in stage 4 and 5 patients. Pocket depth of 4 to 5mm was the most prevalent periodontal problem in controls. In the controls, more individuals had a high DMFT score in comparison to low scores. The scores of decayed teeth and decayed missing filled index were significantly different among the controls and stages 3, 5 and 4 while for missing teeth score, the difference was significant between controls and stages 4 and 5.